2003
DOI: 10.2527/2003.8161508x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding ractopamine (Paylean) on muscle quality and sensory characteristics in three diverse genetic lines of swine1,2

Abstract: The present experiment utilized Berkshire (n = 76), Duroc (n = 81), and high-lean commercial crossbred (n = 75) barrows and gilts with an initial BW of approximately 85.1 kg. Pigs were fed a standard commercial diet (17.6% CP, 1.02% lysine) supplemented with ractopamine hydrochloride at a level of 0 or 10 ppm for 28 d. The experiment was conducted in a randomized complete block design, with animals blocked within genetic line according to litter, gender, and weight, for a total of four blocks per genetic line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
35
4
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 17 publications
(22 reference statements)
15
35
4
8
Order By: Relevance
“…However, barrows had more (P , 0.05) intramuscular fat than gilts, which is in line with the higher carcass fat content observed for castrates, and greater (P , 0.05) dry matter, a finding in accord with the literature (Stoller et al, 2003;Ferná ndez-Dueñ as et al, 2008). These findings are not surprising because castration favours intramuscular fattening of meat (Barton-Gade, 1987).…”
Section: Meat Qualitysupporting
confidence: 83%
See 1 more Smart Citation
“…However, barrows had more (P , 0.05) intramuscular fat than gilts, which is in line with the higher carcass fat content observed for castrates, and greater (P , 0.05) dry matter, a finding in accord with the literature (Stoller et al, 2003;Ferná ndez-Dueñ as et al, 2008). These findings are not surprising because castration favours intramuscular fattening of meat (Barton-Gade, 1987).…”
Section: Meat Qualitysupporting
confidence: 83%
“…Even though initial pH was not significantly affected by gender, ultimate (48 h) pH of barrows was lower (P , 0.05) Stoller et al (2003) reported similar Warner-Bratzler shear force values for the longissimus muscle between barrows and gilts. In addition, these authors observed that the percentage of intramuscular lipid was less in the longissimus muscle from the gilts than barrows (2.27% v. 2.70%, respectively), which concurs with the results of the present study (Table 5).…”
Section: Meat Qualitymentioning
confidence: 58%
“…Porém, outro estudo observou que a densidade energética não altera o consumo em animais suplementados com ractopamina (APPLE et al, 2004). Apesar de haver algumas discordâncias com relação ao efeito da suplementação de ractopamina sobre o consumo alimentar, de modo geral, maiores ganhos de peso foram observados (STOLLER et al, 2003). No presente estudo, porém, o ganho de peso não foi afetado pela ractopamina.…”
Section: Resultsunclassified
“…This agrees with studies in which IMF increased in pigs fed RAC (10 ppm) and had CP (16 %) levels higher than those used here (16,35) . However, in other studies no changes in pork chemical composition were observed in pigs fed diets higher RAC and CP levels: 20 ppm RAC, 17 % CP (36) ; 10 ppm RAC, 16 % CP (37) ; 10 ppm RAC, 17 % CP (38) .…”
Section: Resultados Y Discusiónmentioning
confidence: 90%
“…A certain amount of IMF is considered essential for cooking and maintaining good meat quality (45) . Fat RAC y 16 % de PC) (37) ; (dieta con 10 ppm RAC y 17 % de PC) (38) .…”
Section: Resultados Y Discusiónmentioning
confidence: 99%